Human rights in the emergency situation: constitutional perspective of Latvia - Daškevičs, Artjoms (Riga Graduate School of Law, 2022)
The concept of an emergency situation can be considered a novelty in the international legal system that gained its overwhelming importance due to the spread of Covid-19 pandemics all over the globe. Was the international community ready to employ clear and well-structured mechanisms of emergency situation concept in the context of human rights protection? Was the Latvian legal response to the Covid-19 emergency in the field of human rights protection successful? The “institution of emergency” in the international area was developed by the ECHR, whose ideas were incorporated into Latvian constitutional system and legal order. In that regard, the research uses legal doctrinal method in order to interpret the ECHR “human rights derogations clauses”, interpret the Constitution of the Republic of Latvia on its preparedness to face a Covid-19 emergency, as well as Latvian emergency laws on its compliance with international human rights protection standards and procedures.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Covid-19; European Convention on Human Rights; The Republic of Latvia